Comparative evaluation of 6% cranberry, 10% green tea, 50% aloe vera and 10% sodium ascorbate on reversing the immediate bond strength of bleached enamel: In vitro study - Hena Rahman; Mohd Irfan Ansari; Monika Khangwal; Ravindra Solanki; Shahnaz Mansoori (Elsevier, 2021)
Objectives: The present study aimed to assess antioxidant activity of herbal antioxidants namely 6% cranberry extract, 10% green tea, 50% aloe vera and 10% sodium ascorbate and their effect on reversal of bond strength in bleached enamel. Materials and method: From one hundred and twenty extracted maxillary central incisors enamel blocks of 5 ​× ​5 ​mm were prepared and arbitrarily divided into six experimental groups (n ​= ​20): Group A: no bleaching, Group B: only bleaching protocol, Group C - bleaching ​+ ​6% cranberry extract solution, Group D - bleaching +10% Green Tea extract, Group E − bleaching ​+ ​50% aloe vera extract, Group F - bleaching ​+ ​10% Sodium Ascorbate. After bleaching antioxidants were applied for 10 ​min and were subjected to bonding procedures. The specimens were sectioned into 120 small strips of size (1 ​× ​1 ​× ​8 ​mm). Sixty sticks were analyzed to micro tensile bond strength using Universal testing machine and fractured segment were observed for failure modes (Adhesive, Cohesive and Mixed) under stereomicroscope. Remaining 60 sticks were observed for interface gap between tooth and composite resin under SEM. The %AA (antioxidant activity) was assessed with spectrophotometric analysis. Results: Data was statistically analyzed using ANOVA and Post Hoc Tukey's test. Group A (91.68 ​± ​2.24 Mpa) showed higher mean micro tensile bond strength versus group D (82.14 ​± ​1.45 Mpa), followed by group E (75.26 ​± ​1.92Mpa), group F (63.89 ​± ​1.95Mpa), group C (57.58 ​± ​1.96 Mpa) and least in group B (31.5 ​± ​1.27 Mpa). The %failure mode inferred maximum adhesive mode of failure (86.25%). Conclusion: All the four antioxidants were able to reverse the compromised bond strength comparatively after bleaching maximum being green tea followed by aloe vera, sodium ascorbate, and minimum in cranberry. Clinically significance-: Easily available, biocompatible, cost effectual, and potent herbal antioxidants could be used considerably for immediate esthetic cases where time is a restricting factor.